Information and Communication Technology as a Tool to Achieve Excellence in Algerian Communication Institutions - Benghellab, Imen; Hebbaz, Nahed (جامعة عباس لغرور خنشلة - كلية العلوم الاقتصادية والتجارية وعلوم التسيير, 2023)
The main objective of this paper is to propose a comprehensive and general framework for how to achieve excellence through the optimal use of information and communication technology (TIC) in the Algerian institutions of communication. The descriptive analytical approach was used to analyze the comparative literature and the hypothetical deductive approach was used to develop hypotheses based on theories and draw conclusions based on the questionnaire to reach the main objective. The study found a positive relationship between the dimensions of information and communication technology and the achievement of institutional excellence.
Keywords: تكنولوجيا المعلومات -- مؤسسات الاتصال -- الصناعات المصرفية -- الخدمات اللوجستية